2022
DOI: 10.9745/ghsp-d-21-00648
|View full text |Cite
|
Sign up to set email alerts
|

Community Health Workers in Pandemics: Evidence and Investment Implications

Abstract: A strong and accessible national health system, including at the community level, is critical for pandemic preparedness and response.n Community health workers who are equipped, trained, and paid as part of a well-functioning health system can help prevent epidemics from becoming pandemics and maintain health care delivery amid significant disruption. n To achieve resilient health systems, bi/multilateral aid and private philanthropies need to review their investment practices to replace those that cause harm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
29
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 22 publications
3
29
0
1
Order By: Relevance
“…The FGD findings on workforce development align with recent literature that recommends investing in strengthening the capacity of the health workforce of the Pacific, specifically community health workers [2,12,22]. In 2019, WHO reported the latest available data on density of doctors per 10,000 population by country.…”
Section: Discussionsupporting
confidence: 67%
“…The FGD findings on workforce development align with recent literature that recommends investing in strengthening the capacity of the health workforce of the Pacific, specifically community health workers [2,12,22]. In 2019, WHO reported the latest available data on density of doctors per 10,000 population by country.…”
Section: Discussionsupporting
confidence: 67%
“…Our synthesis showed that apart from routine service delivery CHWs were actively involved in COVID-19 activities such as contact tracing, community education and awareness on COVID-19, screening people with potential COVID-19 symptoms, counselling migrants. Similar roles in both the COVID-19 response and continued delivery of routine services during COVID-19 have been identified by other research, both in some countries included in our research, such as India, Sierra Leone and Kenya and in other contexts, as well as in global syntheses [8,16,18,22,[83][84][85].…”
Section: The Ever-expanding Role Of the Chwsupporting
confidence: 75%
“…Many CHWs experience difficult working conditions and weak employment status during routine times [100], as noted in our synthesis in relation to the normality of fragile financial payments. Action taken to support CHWs during COVID-19 should address the systemic issues affecting CHWs, going beyond short-term measures to support stronger ongoing health system resilience and CHWs well-being [83,100].…”
Section: Plos Global Public Healthmentioning
confidence: 99%
“…And this can be achieved through CHWs. When empowered and properly prepared in terms of training and accessories, CHWs might be among the cost-effective and yet successful approaches in addressing different outbreaks of public health concern 2 .…”
mentioning
confidence: 99%